1993
DOI: 10.1128/mcb.13.10.6231-6240.1993
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Functional NF-κB Site in the Human Interleukin 1β Promoter: Evidence for a Positive Autoregulatory Loop

Abstract: The -300 region of the interleukin 1 beta (IL-1 beta) promoter contains a functional NF-kappa B binding site composed of the decamer sequence 5'-GGGAAAATCC-3'. Probes representing the -300 region or the NF-kappa B site alone interacted with NF-kappa B proteins present in phorbol myristate acetate-, lipopolysaccharide-, or Sendai virus-induced myeloid cell extracts as well as recombinant NFKB1 (p50) and RelA (p65); furthermore, NF-kappa B protein-DNA complex formation was dissociated in vitro by the addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 64 publications
2
29
0
Order By: Relevance
“…43 Additionally, intestinal epithelial cell-specific deletion of IKKB mark-edly reduced DSS-promoted tumor multiplicity, thereby illustrating the necessity of NF-jB signaling in DSS-promoted tumorigenesis. 43 Activation of the NF-jB signaling pathway has been shown to be responsive to excess ROS and is important in the expression of the proinflammatory cytokines, TNFa, 44,45 IL-1B 46 and IL-6. 47 Therefore, the diminution of oxidative stress by Nrf2regulated antioxidative enzymes resulting in decreased NF-jB activation represents a possible anti-inflammatory mechanism for the attenuated DSS-mediated cytokine expression and accumulation of inflammatory cells seen in colons from WT but not N0 mice.…”
Section: Discussionmentioning
confidence: 99%
“…43 Additionally, intestinal epithelial cell-specific deletion of IKKB mark-edly reduced DSS-promoted tumor multiplicity, thereby illustrating the necessity of NF-jB signaling in DSS-promoted tumorigenesis. 43 Activation of the NF-jB signaling pathway has been shown to be responsive to excess ROS and is important in the expression of the proinflammatory cytokines, TNFa, 44,45 IL-1B 46 and IL-6. 47 Therefore, the diminution of oxidative stress by Nrf2regulated antioxidative enzymes resulting in decreased NF-jB activation represents a possible anti-inflammatory mechanism for the attenuated DSS-mediated cytokine expression and accumulation of inflammatory cells seen in colons from WT but not N0 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Other signal receptors that can activate a noncanonical NF-jB signaling cascade via the NF-jB-inducing kinase (NIK) include lymphotoxin B, B-cell activating factor, CD27, and CD40 [61,62]. Over 300 NF-jB target genes have been confirmed in various roles related to inflammation, including cytokines/ chemokines (IFNG [63], IL-1B [64], IL-6 [65], CCL2 [66], TNFA [67]), immunoreceptors (CD40 [68], TNFR1S1B [69], TLR2 [70], NOD2 [71]), cell adhesion molecules (E-selectin [72], ICAM-1 [73], VCAM-1 [74]), stress response genes (PTGS2 [75], NOS2 [76], SOD2 [77]), growth factors (IGFBP1 [78], VEGFC [79]), and other transcription factors (IRF1 [80], MYC [81], TP53 [82]).…”
Section: Inflammation-linked Signaling Cascades: the Nf-jb And Mapk P...mentioning
confidence: 99%
“…Of note, NF-κB is a key transcriptional factor for regulating the inflammatory response [ 43 ]. There are a series of studies indicating that NLRP3, IL-1β, and IL-6 are the target genes of NF-κB [ 41 , 44 , 45 ]. Consistently, our data also showed that Bay11-7082, an NF-κB specific inhibitor, reversed the LPS-induced expression of pro-inflammatory cytokines IL-1β, TNF-α, and IL-6, suggesting that NF-κB activation could participate in regulating neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%